2006
DOI: 10.1186/1465-9921-7-92
|View full text |Cite
|
Sign up to set email alerts
|

IgE sensitisation in relation to flow-independent nitric oxide exchange parameters

Abstract: Background: A positive association between IgE sensitisation and exhaled NO levels has been found in several studies, but there are no reports on the compartment of the lung that is responsible for the increase in exhaled NO levels seen in IgE-sensitised subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 43 publications
8
41
3
Order By: Relevance
“…FeNO 50 was also related to FEV 1 . Atopy was related not only to increased FeNO 50 and J 0 aw NO but also to unadjusted Calv NO , which contradicts a previous study from our group (41). This might be explained by the population-based setting of the previous study and the relatively small size of the effect: a large population of patients with asthma as in the present study is probably required to find significant differences.…”
Section: Discussioncontrasting
confidence: 82%
“…FeNO 50 was also related to FEV 1 . Atopy was related not only to increased FeNO 50 and J 0 aw NO but also to unadjusted Calv NO , which contradicts a previous study from our group (41). This might be explained by the population-based setting of the previous study and the relatively small size of the effect: a large population of patients with asthma as in the present study is probably required to find significant differences.…”
Section: Discussioncontrasting
confidence: 82%
“…There was no significant interaction between sensitization and exposure. In adults with cat sensitization, FeNO did not change significantly with cat exposure (17,21). We also found that cat ownership was not associated with a change in FeNO.…”
Section: Discussionsupporting
confidence: 55%
“…Although there may be a volunteer bias, we avoided further selection influences that occur when subjects have been referred to a clinical setting. There may be misclassification on diagnoses, but we relied on the reported diagnosis of asthma and allergies by a physician, as described in previous reports (21,36). For the categorization of allergies with or without asthma, it would be preferable to confirm atopy using allergy skin testing, as had been performed in previous, somewhat smaller studies (2,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Holm adjustments for multiple comparisons were also reported in the models described in Tables III and E5. Because atopy is related to FENO values, 21 a multiple logistic regression model not adjusted for hay fever (used as proxy for atopy in this study) was also reported (see Table E5). A P value of less than .05 was considered statistically significant.…”
Section: Statistical Analysesmentioning
confidence: 99%